Leadership Management in Delivering Educational Services in Higher Education - Bendriyanti, Rita Prima; Suwarni, Suwarni; Dewi, Citra; Sukirdi, Sukirdi (Universitas Trunojoyo Madura, 2024)
This study aims to analyze the role of leadership management in improving the quality of educational services in higher education through a qualitative approach using literature study analysis. The research focuses on exploring transformational, situational, and participative leadership theories as the foundation for designing effective managerial strategies. The findings reveal that the implementation of adaptive and innovative leadership models not only enhances institutional internal performance but also strengthens academic service capacity through collaboration, human resource empowerment, and responsiveness to the dynamic needs of stakeholders. Further analysis demonstrates that integrating participative and transformational leadership principles fosters an inclusive educational environment oriented toward continuous improvement. These findings affirm the critical synergy between flexible leadership styles and structured management policies in driving the transformation of higher education services. The study provides practical recommendations for policymakers and higher education stakeholders to adopt holistic leadership approaches aligned with contemporary challenges, while opening avenues for further research on managerial innovations in the education sector.